Music in school teaching processes through the centuries - Batņa, Liene (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Acquisition of music terms is a significant component in a contemporary music lesson in a comprehensive school nowadays. Methodology of teaching music as a separate branch in Latvia started developing in the beginning of the 20th century with the analysis of music educators’ experience published by I. Palevics. However, music as a subject at school has a longer history therefore it would be important to explore the pedagogic role of music in different periods because during music lessons not only students’ musicality and personal development are facilitated but also the tradition of singing which includes the tradition of Song Festival is maintained. In 2008 the tradition of Baltic Song and Dance Festival was included in the UNESCO List of Representative Human Non-material Culture Heritage. Therefore it is important to explore what pedagogic aspects had provided the vital capacity of Song and Dance Festival tradition throughout centuries. The aim of the article is to analyze the place of music in the pedagogic process in different historic periods. When analyzing the topicality of the article, following aim has been nominated: to explore - how the music learning traditions are formed in Latvian schools, polyphony and choir traditions, teacher education, the knowledge of music teaching inheriting from generation to generation until the.